![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(\left(x-1\right)^3+\left(2-x\right)\left(4+2x+x^2\right)+3x\left(x+2\right)=17\)
<=> \(x^3-3x^2+3x-1+\left(2-x\right)\left(x+2\right)^2+3x^2+6x=17\)
<=> \(x^3+9x-1+2\left(x+2\right)^2-x\left(x+2\right)^2=17\)
<=> \(x^3+9x-1+2\left(x^2+2x+1\right)-x\left(x^2+2x+1\right)=17\)
<=> \(x^3+9x-1+2x^2+4x+2-x^3-2x^2-x=17\)
<=> \(12x+1=17\)
<=> \(12x=16\)
<=> \(x=\frac{4}{3}\)
b/ \(\left(x+2\right)\left(x^2-2x+4\right)-x\left(x^2-2\right)=15\)
<=> \(\left(x+2\right)\left(x-2\right)^2-x\left(x^2-2\right)=15\)
<=> \(x\left(x-2\right)^2-x\left(x^2-2\right)+2\left(x-2\right)^2=15\)
<=> \(x\left(x^2-2x+1\right)-x\left(x^2-2\right)+2\left(x-2\right)^2=15\)
<=> \(x\left[x^2-2x+1-\left(x^2-2\right)\right]+2\left(x-2\right)^2=15\)
<=> \(x\left(x^2-2x+1-x^2+2\right)+2\left(x-2\right)^2=15\)
<=> \(x\left(3-2x\right)+2\left(x^2-2x+1\right)=15\)
<=> \(3x-2x^2+2x^2-4x+2=15\)
<=> \(2-x=15\)
<=> \(x=-13\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 6x(x - 3) = 6x2 - 24 + 3x
<=> 6x2 - 18x = 6x2 - 24 + 3x
<=> 6x2 - 18x - 6x2 - 3x = -24
<=> -21x = -24
<=> x =8/7
Vậy S = {8/7}
b) \(\frac{x-1}{4}-\frac{5-2x}{9}=\frac{3x-2}{3}\)
<=> \(9\left(x-1\right)-4\left(5-2x\right)=12\left(3x-2\right)\)
<=> 9x - 9 - 20 + 8x = 36x - 24
<=> 17x - 36x = -24 + 29
<=> -19x = 5
<=> x = -5/19
vậy S = {-5/19}
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(=2xy^2\left(x^2+8x+15\right)\)
\(=2xy^2\left[\left(x^2+8x+16\right)-1\right]\)
\(=2xy^2\left[\left(x+4\right)^2-1\right]\)
\(=2xy^2\left(x+4+1\right)\left(x+4-1\right)\)
\(=2xy^2\left(x+5\right)\left(x-3\right)\)
mấy câu sau tự làm nha :*
b,=(x^2-10x+25)-4
=(x-5)^2-2^2
=(x-5-2)(x-5+2)
=(x-7)(x-3)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.x2-9
= (x-3)(x+3)
2. -2x2+2x+12
= -2x2+6x-4x+12
= -2x(x+2)+6(x+2)
= (x+2)(-2x+6)
4. -2x2+2x+24
= -2x2+8x-6x+24
= -2x(x+3)+8(x+3)
= (x+3)(-2x+8)
6. x2-5x+4
= x2-4x-x+4
= x(x-1) -4(x-1)
= (x-1)(x-4)
8. x2-7x+6
= x2-6x-x+6
= x(x-1)-6(x-1)
= (x-1)(x-6)
9. x2+5x+4
= x2+4x+x+4
= x(x+1)+4(x+1)
=(x+1)(x+4)
10. x2+7x+6
= x2 +x+6x+6
= x(x+1)+6(x+1)
= (x+6)(x+1)
K nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x\left(x+1\right)-x\left(x-5\right)=6\Leftrightarrow x^2+x-x^2+5x=6\)
\(\Leftrightarrow x=1\)
b, \(4x^2-4x+1=0\Leftrightarrow\left(2x-1\right)^2=0\Leftrightarrow x=\frac{1}{2}\)
c, \(x^2-\frac{1}{4}=0\Leftrightarrow\left(x-\frac{1}{2}\right)\left(x+\frac{1}{2}\right)=0\Leftrightarrow x=\pm\frac{1}{2}\)
d, \(5x^2=20x\Leftrightarrow5x^2-20x=0\Leftrightarrow5x\left(x-4\right)=0\Leftrightarrow x=0;4\)
e, \(4x^2-9-x\left(2x-3\right)=0\Leftrightarrow4x^2-9-2x^2=3x\Leftrightarrow2x^2-9-3x=0\)
\(\Leftrightarrow\left(2x+3\right)\left(x-3\right)=0\Leftrightarrow x=-\frac{3}{2};3\)
f, \(4x^2-25=\left(2x-5\right)\left(2x+7\right)\Leftrightarrow\left(2x-5\right)\left(2x+5\right)-\left(2x-5\right)\left(2x+7\right)=0\)
\(\Leftrightarrow-2\left(2x+5\right)=0\Leftrightarrow x=-\frac{5}{2}\)
a) x( x + 1 ) - x( x - 5 ) = 6
⇔ x2 + x - x2 + 5x = 6
⇔ 6x = 6
⇔ x = 1
b) 4x2 - 4x + 1 = 0
⇔ ( 2x - 1 )2 = 0
⇔ 2x - 1 = 0
⇔ x = 1/2
c) x2 - 1/4 = 0
⇔ ( x - 1/2 )( x + 1/2 ) = 0
⇔ \(\orbr{\begin{cases}x-\frac{1}{2}=0\\x+\frac{1}{2}=0\end{cases}}\Leftrightarrow x=\pm\frac{1}{2}\)
d) 5x2 = 20x
⇔ 5x2 - 20x = 0
⇔ 5x( x - 4 ) = 0
⇔ \(\orbr{\begin{cases}5x=0\\x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=4\end{cases}}\)
e) 4x2 - 9 - x( 2x - 3 ) = 0
⇔ ( 2x - 3 )( 2x + 3 ) - x( 2x - 3 ) = 0
⇔ ( 2x - 3 )( 2x + 3 - x ) = 0
⇔ ( 2x - 3 )( x + 3 ) = 0
⇔ \(\orbr{\begin{cases}2x-3=0\\x+3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{3}{2}\\x=-3\end{cases}}\)
f) 4x2 - 25 = ( 2x - 5 )( 2x + 7 )
⇔ ( 2x - 5 )( 2x + 5 ) - ( 2x - 5 )( 2x + 7 ) = 0
⇔ ( 2x - 5 )( 2x + 5 - 2x - 7 ) = 0
⇔ ( 2x - 5 )(-2) = 0
⇔ 2x - 5 = 0
⇔ x = 5/2
Quy đồng